The effectiveness of social media use among university students in Malaysia / Wan Nurul Suhana Fatma Mat Isa... [et al.] - Mat Isa, Wan Nurul Suhana Fatma; Mohd Rodzi, Nurul Ainaa; Libasin, Zuraira; Idris, Nur Azimah; Mazeni, Noor Azizah; Jaafar, Rosley (Unit Penulisan Dan Penerbitan JSKM, 2022)
Social media has now become an integral part of a student’s life. It may harm their productivity, especially their time management. On the positive side, social media provides students with learning opportunities and the chance to interact with others during online distance learning. This study focuses on determining whether the students’ average time spent on social media is related to their CGPA results. In addition, this study highlighted either gender effects of social media use by students. In this study, a questionnaire designed by QuestionPro was adopted and revised. It was distributed through social media platforms and gathered 50 respondents. The relationship between average time spent on social media with CGPA results was analysed using the Chi-Square test of independence. In contrast, the independent sample t-test was used to analyse the effectiveness of social media use by students’ gender. Based on the results, the Chi-Square test (p<0.001) shows that social media usage impacts students’ performance, where students who get high CGPA results spend minimum average time daily on social media. The independent sample t-test shows that the effectiveness of social media used between males (M=3.526, SD=0.697) and females (M=3.645, SD=0.985) are not statistically significant t(48)=-0.459, p=0.648.SD=0.697).